Jasminanthes laotica (Apocynaceae, Asclepiadoideae), the first new species of Jasminanthes described from Laos - Ding, Hong-Bo; Yang, Bin; Zeng, Xiao-Dong; Tan, Yun-Hong (Phytotaxa, 2019)
Jasminanthes laotica (Apocynaceae, Asclepiadoideae), a new species from northern Laos is described, illustrated and a diagnostic key to the species of Jasminanthes Blume is given in this paper. J. laotica is allied to J. xuanlienensis T.B. Tran & Rodda, but can be distinguished by its longer sepals, obtuse to subcordate lamina base, and bright yellow of the inner corolla lobes, salmon-pink of the outer corolla lobes.